Are they really so different? Climate change rule development in the USA and UK. Issue 1 (14th April 2014) - Cook, Jeffrey; Rinfret, Sara
<x xml:space="preserve">Abstract</x> Climate change is an increasingly complex and global environmental issue. As a result, scholars have begun to compare the efforts of specific countries such as the UK and the USA in dealing with climate change. However, missing within this comparative literature is a discussion of the important role that administrative agencies play in implementing climate change policy through rulemaking. More specifically, it is unclear how administrative processes may impact or explain variations in the policy implemented within a given country. In fact, it has been over 25 years since Vogel's work compared the regulatory processes of the USA and UK. As a result, this paper's interviews with agency rule writers in both countries provide an updated comparison of their rulemaking processes, which is essential to understanding why countries may vary in the climate change policy they implement. Copyright © 2014 John Wiley & Sons, Ltd.